Schoolchildren’s physical education competency versus physical fitness self-rates: survey and analysis - Lukmanova, N.B.; Malinin, A.V.; Pukhov, D.N.; Abramova, T.F. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to survey the schoolchildren’s reported physical education competency versus their physical fitness self-rates and run a correlation analysis. Methods and structure of the study. We run a questionnaire survey of the 11-year-old schoolchildren (n= 485) under the ongoing international Health and Behavior of Schoolchildren (HBSC) Research Project and grouped by their physical education competency self-rates into reportedly competent Group 1 and incompetent Group 2. Then we processed the group questionnaire survey data by a statistical toolkit χ2 criterion and made a physical education competency versus physical fitness correlation analysis to find correlations of the reported physical education competency with the physical fitness elements. Results and conclusion. The survey and analysis of the schoolchildren’s reported physical education competency versus their physical fitness self-rates found them significantly correlated. The 11-year-olds with excellent and good physical education competency and physical fitness self-rates demonstrated significantly higher physical education competency / physical fitness correlations in virtually every physical fitness element than their lower self-rated peers.